2021
DOI: 10.1186/s12916-021-02116-z
|View full text |Cite
|
Sign up to set email alerts
|

Activated gut-homing CD8+ T cells for coeliac disease diagnosis on a gluten-free diet

Abstract: Background The diagnosis of coeliac disease (CD) in individuals that have started a gluten-free diet (GFD) without an adequate previous diagnostic work-out is a challenge. Several immunological assays such as IFN-γ ELISPOT have been developed to avoid the need of prolonged gluten challenge to induce the intestinal damage. We aimed to evaluate the diagnostic accuracy of activated gut-homing CD8+ and TCRγδ+ T cells in blood after a 3-day gluten challenge and to compare it with the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The findings of Han et al. ( 6 ) were used by our research group to try a new test to diagnose CD and thus we showed that the study of activated gut-homing CD8 + T cells by flow cytometry offered 95% specificity and 97% sensitivity for detecting seropositive CD ( 39 ). This test has a presumed easy implementation in clinical practice.…”
Section: Blood Lymphogrammentioning
confidence: 89%
See 2 more Smart Citations
“…The findings of Han et al. ( 6 ) were used by our research group to try a new test to diagnose CD and thus we showed that the study of activated gut-homing CD8 + T cells by flow cytometry offered 95% specificity and 97% sensitivity for detecting seropositive CD ( 39 ). This test has a presumed easy implementation in clinical practice.…”
Section: Blood Lymphogrammentioning
confidence: 89%
“…The authors concluded that the celiac lymphogram was associated with a high level of diagnostic evidence either against or in favor of CD in patients with SNVA. The celiac lymphogram has also been shown to be a useful tool to consider Marsh 1 lesions as CD ( 29 , 31 , 32 , 39 41 ). Using dermatitis herpetiformis as a model disease in which there are gluten-related symptoms despite of a non-atrophic enteropathy, even with negative celiac serology in a high percentage of patients, Popp and Mäki argue about the existence of a ‘celiac trait’, consisting in a Marsh 1 lesion, positive celiac genetics and increase in γδ + cells, that should be identified and treated since they present clinical and histological remission after a GFD ( 42 ).…”
Section: Intraepithelial Lymphogrammentioning
confidence: 99%
See 1 more Smart Citation